Effectiveness of cover crop species in oil palm weed management - Samadany, Batoul (2013)
Sustainable oil palm cultivation is gaining popularity in Malaysia. Currently alternative strategies to chemical herbicides for weed control have received widespread attention. Hence field experiments were designed to compare the effect of cover crops on the response of oil palms and weeds. Six ground cover treatments viz. Axonopus compressus, Calopogonium caeruleum + Centrosema pubescens, Mucuna bracteata, Pueraria javanica + Centrosema pubescens, weeded and un-weeded were evaluated. Initial weed composition revealed two dominant weed species viz. Borreria latifolia and A. compressus. A. compressus, M. bracteata and other legume cover crops achieved 100% coverage at 3, 6 and 9 months after planting, respectively. Cover crops and un-weeded treatments produced comparablevegetation biomass. Cover crops were found to be effective in controlling weeds. The un-weeded treatment favored Paspalum conjugatum and A. compressusas the dominant species. In the A. compressus and C. caeruleum + C. pubescensthe associated weed species with highest dominance was Asystasia gangetica, while the weedsA. compressus and A. gangeticawere associated with M. bracteata and P. javanica + C. pubescens. In the weeded treatment B. latifolia was dominant. The A. compressus treatment had the lowest species richness and diversity. The A. compressus treatment showed yield difference with weeded plot at between 18 to 24 months after planting. The cover crops did not influence nutrient levels or photosynthesis rate of oil palm relative to the un-weeded and weeded. The M. bracteata treatment increased K and Ca in the soil. Results of smothering effects of cover crops on P. polystachion and A. gangetica revealed that A. gangetica was a weaker competitor than P. polystachion. Legume cover crops had a higher relative yield when grown in mixtures with A. gangetica than in the monoculture. The superior competition of legume cover crops was due to the higher canopy height and high leaf area index. With P. polystachion, the dry weight per plant, leaf area and shoot numbers increased as its proportion decrease in the mixture.The competitive ability of A. compressusagainestA. gangetica was investigated under contrasting sunlight intensity. Suppression of A. gangetica by A. compressus occurred under full sunlight, irrespective of plant density, but this ability was reduced under shade as density decreased. The possibility of allelopathic effects of cover crop litter on A. gangetica and P. polystachionwas tested. Cover crop litter leachates decreased the germination and seedling length of A. gangeticaand P. polystachion. The cover crops leachates also delayed the germination of A. gangetica. The effect of litter leachate-amended soil on root and shoot length, dry weight and chlorophyll concentration of A. gangetica and P. polystachion seedlings revealed that theywere not sensitive to the leachate amended soils of cover crop. Study on the fate of cover crop litter phenolics in the soil showed that the phenolic compounds in cover crop litter is unstable in the soil system for a considerable period of time.